Kafka's creatures animals, hybrids, and other fantastic beings - Lucht, Marc 1969-; Yarri, Donna (IG library, 2010)
There are few literary authors in whose work animals and other creatures play as prominent a role as they do in Franz Kafka's. Exploring multiple dimensions of Kafka's incorporation of nonhuman creatures into his writing, this volume is the first collection in English of essays devoted to illuminating this important and ubiquitous dimension of his work. The chapters here are written by an array of international scholars from various fields, and represent a diversity of interpretive approaches.